2012
DOI: 10.2166/nh.2012.010
|View full text |Cite
|
Sign up to set email alerts
|

Water and nutrient simulations using the HYPE model for Sweden vs. the Baltic Sea basin – influence of input-data quality and scale

Abstract: Water resource management is often based on numerical models, and large-scale models are sometimes used for international strategic agreements. Sometimes the modelled area entails several political entities and river basins. To avoid methodological bias in results, methods and databases should be homogenous across political and geophysical boundaries, but this may involve fewer details and more assumptions. This paper quantifies the uncertainty when the same model code is applied using two different input data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 0 publications
1
66
0
2
Order By: Relevance
“…The Swedish application (S-HYPE) has also been evaluated against independent internal model variables such as snow pack, lake water level and groundwater fluctuation (Arheimer et al 2011a, b), which also makes that model application more trustworthy. Arheimer et al (2012) thus compared model results for Sweden using both the S-HYPE and the Balt-HYPE and, in short, that study showed that especially water discharge was much better simulated using the S-HYPE, with most relative errors are \10 % for S-HYPE and \25 % for Balt-HYPE. Both the applications normally reproduced mean concentration for N within 25 % of the observed mean values, while P showed a larger scatter.…”
Section: Uncertainties In the Results From The Model Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Swedish application (S-HYPE) has also been evaluated against independent internal model variables such as snow pack, lake water level and groundwater fluctuation (Arheimer et al 2011a, b), which also makes that model application more trustworthy. Arheimer et al (2012) thus compared model results for Sweden using both the S-HYPE and the Balt-HYPE and, in short, that study showed that especially water discharge was much better simulated using the S-HYPE, with most relative errors are \10 % for S-HYPE and \25 % for Balt-HYPE. Both the applications normally reproduced mean concentration for N within 25 % of the observed mean values, while P showed a larger scatter.…”
Section: Uncertainties In the Results From The Model Experimentsmentioning
confidence: 99%
“…S2, Electronic supplementary material). A more comprehensive overview of model performance can be found in Arheimer et al (2012), including several goodness-of-fit statistics and a sensitivity study. In general, the Balt-HYPE model overestimates nutrient discharge on an annual basis, especially in the southern part of the catchment.…”
Section: Balt-hype Model Estimation Of Nutrient Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…Uhlenbrook and Sieber, 2005;Vaché and McDonnell, 2006;Iorgulescu et al, 2007;McGuire et al, 2007;Page et al, 2007;Fenicia et al, 2010;Lindström et al, 2010;Lyon et al, 2010b;Birkel et al, 2011a,c;Arheimer et al, 2012;Capell et al, 2012b;Bertuzzo et al, 2013). For example, Dunn et al (2007Dunn et al ( , 2010) used a conceptual model in the context of virtual experiments (cf.…”
Section: Hrachowitz Et Al: What Can Flux Tracking Teach Us About mentioning
confidence: 99%
“…The HYPE (Hydrological Predictions for the Environment) model is a process-based hydrological model developed for high-resolution multi-basin applications, which has been applied on various spatial scales (from tens to millions of square kilometers) and hydroclimatological conditions (Lindström et al, 2010;Strömqvist et al, 2012;Arheimer et al, 2012;Andersson et al, 2015;Gelfan et al, 2017). The model is based on a semi-distributed approach where the hydrological system is represented by a network of sub-basins, which are further divided into classes that can be selected to represent combinations of soil type and land cover or elevation zones.…”
Section: Hype Modelmentioning
confidence: 99%